Pengenaan PPN, PPnBM, dan PKB Progresif Terhadap Minat Beli Mobil di Palembang - Evisesti, Ulya; Desitama Anggraini, Leriza; Meisari, Vhika (Jurnal Dinamika Ekonomi dan Bisnis, 2025)
Taxes are mandatory contributions levied by the government from the public and used for public purposes to promote societal welfare. This study aims to analyze the influence of Value-Added Tax (VAT), Sales Tax on Luxury Goods (STLG), and Motor Vehicle Tax (MVT) with progressive rates on the purchase interest of four-wheeled vehicles in Palembang City, specifically at SAMSAT Talang Kelapa in 2023. This research uses a quantitative method with primary data obtained through literature review, observation, interviews, and the distribution of questionnaires to 100 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the imposition of VAT, STLG, and MVT with progressive rates has a positive influence on the purchase interest of four-wheeled vehicles. Although high tax rates may reduce the purchasing power of some individuals, others continue to make purchases due to lifestyle and social status factors. The increase in progressive rates implemented in Palembang City also impacts the number of vehicle ownership and local tax revenue. Furthermore, the implementation of this tax policy is expected to help control the number of motor vehicles, aligning with the Sustainable Development Goals (SDGs) related to sustainable cities and communities. This study contributes to the government in designing more effective tax policies and to the public in understanding the impact of progressive taxes on vehicle purchase decisions. The findings are also expected to serve as a reference for further studies on taxation and its impact on regional economies